Business University Incubators in Algeria: A New Mechanism for the Promotion of Start-ups - M’sila University Incubator Model - Samah EL CHEIKH,; Amina MEZIANE,; Abderrahmane BENANTAR, (Journal of North African Economies, 2025)
This study tackles the topic of university incubators and their importance in supporting and accompanying start-ups in Algeria with a model review of the incubator of the University of M’sila. This is in light of the growing interest in these institutions, which are relied upon to be the basis of the new economic model that aims to achieve economic development outside the hydrocarbon sector. In this context, this research aims to clarify the role and reality of start-ups and university business incubators in Algeria, and focus on the business incubator of the University of M'sila as a model. The results of the analysis and study confirmed the essential role of university business incubators in supporting and accompanying the creation of start-ups by university students and researchers. Based on the experience of the University of M'Sila incubator, the first and most active and dynamic university incubator in Algeria in terms of the number of incubated projects, the number of “Innovative Project” marks obtained, the number of files filed for patents, as well as the number of training courses offered, demonstrations and competitions in which they participate. All project holders interviewed emphasize the positive impact and the importance of the M’sila incubator and the services it provides, enabling them to lead in their entrepreneurial path and embody their start-ups.